Justice-Based Legal Theory in Shaping the Notary's Role: Balancing Law and Equity - Wiranatakusumah, Sarah Arifin (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
This study examines the application of legal theory in the notary profession through the lens of justice-based balance theory. As public officials, notaries represent the state in civil matters and must navigate complex legal and social dynamics while ensuring justice, legal certainty, and utility—three often-conflicting legal values. Prioritizing justice is essential, as it embodies the ultimate goal of law: fostering societal fairness. Notaries face significant risks of legal entanglement—criminal, civil, or administrative—stemming from the deeds they create, highlighting the urgency for robust legal protections. By addressing these challenges, this research contributes a novel perspective on integrating justice-based balance theory into notarial practices, ensuring notaries can uphold their duties effectively while minimizing legal vulnerabilities. The findings underscore the necessity of a justice-centered approach, offering insights for strengthening notarial governance and enhancing legal frameworks to align with societal needs and values.